Perceived Impacts of Solo International Performing Arts 2025 on Hotel Occupancy: A Stakeholder Perspective - Dicky Tinton Hermanto; Agus Solikhin; Darmaesti; Sugiman (Jurnal Pariwisata Nusantara (JUWITA), 2026)
Purpose: This study aims to develop a stakeholder collaboration framework for optimizing the contribution of cultural events to hotel occupancy, using the 2025 edition of Solo International Performing Arts (SIPA) — a cultural event consistently held in Surakarta City and part of the Karisma Event Nusantara programme — as the case. Method: A qualitative case study approach was applied through in-depth interviews with five stakeholder groups, namely the SIPA Foundation, Kusuma Sahid Prince Hotel, Hotel FIM by Zigna Yosodipuro, a travel agent, and the Surakarta City Culture and Tourism Office; data were analyzed using thematic analysis. Result: All stakeholders regard SIPA as a strategically important cultural event, yet its contribution to hotel occupancy could not be directly substantiated because of the absence of integrated daily occupancy-monitoring data and the lack of formal regional budget regulation for independently funded events. Contribution: This study extends Stakeholder Theory by proposing a stakeholder collaboration framework that integrates tourism package development, event-experience innovation, and real-time hotel occupancy monitoring. The framework offers a practical governance model for reducing data asymmetry, strengthening cross-sector collaboration, and translating the potential of cultural events into measurable improvements in hotel occupancy and destination competitiveness.